2018
DOI: 10.1007/s12273-018-0428-x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a magnetocaloric heat pump in a low-energy residential building

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Thus, two different types of the regenerator cassettes were selected for the numerical analysis presented in this article. The size of the first type of the regenerators is based on the cassettes of the MagQueen, which is a magnetocaloric heat pump, developed at DTU Energy (Dall'Olio et al, 2017;Johra et al, 2018). Originally, the cassettes of MagQueen were tapered in order to obtain higher COP.…”
Section: Amr Geometriesmentioning
confidence: 99%
“…Thus, two different types of the regenerator cassettes were selected for the numerical analysis presented in this article. The size of the first type of the regenerators is based on the cassettes of the MagQueen, which is a magnetocaloric heat pump, developed at DTU Energy (Dall'Olio et al, 2017;Johra et al, 2018). Originally, the cassettes of MagQueen were tapered in order to obtain higher COP.…”
Section: Amr Geometriesmentioning
confidence: 99%
“…2 can look different from the ones of publications reporting COPs of the sole AMR operation. The MCHP of the current study can produce 2600 W of useful heating power with an average seasonal COP of 3.93 when operating at fluid flow rate of 2200 L/h and with a rotation frequency of 1 Hz [37].…”
Section: Magnetocaloric Technologymentioning
confidence: 90%
“…The AMR system principle is described in detail in the articles of Engelbrecht et al [28] and Lei et al [35]. A previous study from the ENOVHEAT project [37] numerically demonstrated for the first time that such a magnetocaloric heat pump (MCHP) can be implemented in a low-energy single family house and provide for its space heating needs under cold weather climate conditions (Denmark). In this project, the MCHP is used solely for indoor space heating because domestic hot water production requires a higher temperature span.…”
Section: Magnetocaloric Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Albertini et al conducted a preliminary study of a prototype rotary magnetic refrigerator consisting of four static active magnetic regenerators and a rotor with two permanent magnet assemblies. In 2018, Johra et al reported the numerical evaluation of a magnetic heat pump that could be integrated into a single hydronic loop including a ground‐source heat exchanger and a radiant under‐floor heating system. The device was designed for a maximum heating power of 2600 W and consisted of 13 regenerators arranged in a trapezoidal form and with beds packed with 0.45 mm spheres.…”
Section: Magnetocaloric Refrigeration and Heat Pumpingmentioning
confidence: 99%